Experimental realization of high-fidelity teleportation via a non-Markovian open quantum system - Z.-D. Liu; Y.-N. Sun; B.-H. Liu; C.-F. Li; G.-C. Guo; S. Hamedani Raja; H. Lyyra; J. Piilo (American Physical Society, 2022)
Open quantum systems and study of decoherence are important for our fundamental understanding of quantum physical phenomena. For practical purposes, a large number of quantum protocols exist that exploit quantum resources, e.g., entanglement, which allows us to go beyond what is possible to achieve by classical means. We combine concepts from open quantum systems and quantum information science and give a proof-of-principle experimental demonstration—with teleportation—that it is possible to implement efficiently a quantum protocol via a non-Markovian open system. The results show that, at the time of implementation of the protocol, it is not necessary to have the quantum resource in the degree of freedom used for the basic protocol—as long as there exists some other degree of freedom or the environment of an open system, which contains useful resources. The experiment is based on a pair of photons, where their polarizations act as open system qubits and frequencies as their environments, while the path degree of freedom of one of the photons represents the state of Alice's qubit to be teleported to Bob's polarization qubit.